SISTEM PAKAR MENGIDENTIFIKASI PENYAKIT PADA SAPI MENGGUNAKAN METODE FORWARD CHAINING - Marwan Hakim (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2022)
Seeing the current state of society, they rarely pay attention to diseases of their pets/livestock and how to handle them. Livestock disease can be caused by many things, such as poor housing management, attacks by infectious agents, viruses, bacteria, parasites, fungi. Even today, disease in cattle is found to be caused by prions, which are a type of protein molecule that has changed its configuration. Not to mention the cattle breeders were shocked by Foot and Mouth Disease (FMD), which spreads very quickly. FMD virus enters the animal's body through the mouth or nose and the virus multiplies in the epithelial cells in the nasopharynx. The FMD virus then enters the blood and multiplies in the lymph glands and epithelial cells in the mouth and feet (scratches on the feet) resulting in sores/blisters. Technological developments demand that all problems must be resolved quickly and precisely. So researchers are trying to overcome this problem by creating an expert system application to identify diseases in cattle. The discussion in this study contained 18 cow symptoms and concluded 6 cow diseases. In general, the goals and benefits to be achieved in this research are to make it easier for all of us and more specifically for the community to identify diseases in cattle and how to treat them.